Therapeutic dilemma and clinical issues in management of the button battery ingestion: a case report and literature review - Olsi Agolli; Arjola Agolli; Namrata Hange; Kuchalambal Agadi (SpringerOpen, 2021)
Abstract The incidence of button battery ingestion in children less than 6 years, from year 1985 to 2019 was 59,000 and it is still a clinical challenge for pediatricians. Objects which are commonly ingested are large amounts of food, coins, toy parts, jewels, batteries, sharp materials and non-metallic sharp objects. It is an increased incidence of mortality and morbidity due to button battery ingestion, compared to accidental ingestion of other objects, due to its small size, and because of its potent source of energy. A literature search was carried out to evaluate the challenges in diagnosing, treatment, and follow-up of button battery ingested cases in children. A total of 36 original articles were included for the review. Conclusions: Button batteries can quickly cause severe damage to the mucosal lining of the GI tract. Esophageal button batteries require emergency removal because they can cause serious complications leading to hemorrhage, and death. In children, where the button battery has passed the esophagus watchful management should be made. In the majority of cases, the button batteries with a diameter less than 2 cm lodged in the stomach will pass spontaneously with no complications. However, asymptomatic children may be followed up with X-rays to assess progression up to 10-14 days after ingestion. Endoscopic or surgical removal may be required to prevent intestinal perforation with peritonitis. Symptomatic children will always need a consultation with a pediatric surgeon for surgery no matter where the button battery is placed in the GI tract. Developing countries shall adopt surveillance and reporting systems for BBI ingestion and related complications and it is recommended as essential to have management protocols in place for button batteries ingestion.